2020
DOI: 10.1103/physrevb.101.094507
|View full text |Cite
|
Sign up to set email alerts
|

Quasiclassical free energy of superconductors: Disorder-driven first-order phase transition in superconductor/ferromagnetic-insulator bilayers

Abstract: In the seminal work by G. Eilenberger, Z. Phys. 214, 195 (1968), a closed-form expression for the free energy of inhomogeneous spin-singlet superconductor in terms of quasiclassical propagators has been suggested. However, deriving this expression and generalizing it for superconductors or superfluids with general matrix structure, e.g., spin-triplet correlations, has remained problematic. Starting from the Luttinger-Ward formulation, we discuss here the general solution. Besides ordinary superconductors with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 70 publications
(137 reference statements)
0
4
0
Order By: Relevance
“…Although the splitting h in the ballistic model depends on the momentum direction, it is expected to be averaged by disorder of the bulk and the interface, and by Fermi liquid interactions [24,26,31,42]. For thin films, in this case one expects [26] h…”
Section: Non-reciprocal Transport In Hybrid Superconductor/ Ferromagn...mentioning
confidence: 99%
“…Although the splitting h in the ballistic model depends on the momentum direction, it is expected to be averaged by disorder of the bulk and the interface, and by Fermi liquid interactions [24,26,31,42]. For thin films, in this case one expects [26] h…”
Section: Non-reciprocal Transport In Hybrid Superconductor/ Ferromagn...mentioning
confidence: 99%
“…Namely, Tokuyasu et al [26] have shown that in the clean limit, this phase transition is always of the second order. However, a recent work established that even a small amount of impurity scattering restores the possibility of a first-order phase transition [43]. We assume here the diffusive limit, which is well justified for Al films due to their intrinsic disorder.…”
Section: Critical Temperature Of a Fi/s Bilayermentioning
confidence: 99%
“…This can be achieved, for example, in EuS/Al systems [2,4,5,7,24], where the interfacial exchange interaction leads to a sharp spin-splitting in S layers with thicknesses smaller than the coherent length. On the theoretical side, the effect of the interfacial exchange field and the induced spin-splitting on the superconducting state has been studied in numerous works [5,[25][26][27]. Most of these works assume a homogeneous spin-splitting field.…”
Section: Introductionmentioning
confidence: 99%